A study protocol for HEalth-Related quality of life-intervention in survivors of Breast and other cancers experiencing cancer-related fatigue using TraditionAL Chinese Medicine: the HERBAL trial - Yap, N.Y. (BioMed Central Ltd, 2021)
10.1186/s13063-020-04810-4